Extension of Existing Platform of Kochi Metro to Accommodate More Train-Cars - Akul Nair, M; Sofi, A; Kannan, V (International Journal of Engineering and Technology, 2018)
The metro rail being successfully a mode of transportation that is by far largely the main and the most used service for easier travelling is posed with restriction limited due to the existing design. Kochi metro being elevated throughout has provision of extension of platform to allow more passenger thereby more train cars. In this paper an attempt is made to provide easy, efficient and low cost method of extension of platform using steel plate girders as the main super structure component. The model is developed and analysed in SAP2000 which is then checked for deflection and reinforcement criterion. A 3D finite element model of the composite steel concrete girder is developed using ABAQUS to observe the load and stress transfer as well as the behaviour of shear studs.Â Â